Hackerspace Network: Prefiguring Technopolitical Futures? - R. Murillo, Luis Felipe (American Anthropologist, 2020)
Under the practical symbol of "hacking," computer expertise has been translated into renewed forms of political action in the past two decades. In this article, I examine this phenomenon through the study of self‐organized collectives for technoscientific experts who identify as "hackers." Based on multisited field research in global cities of the Pacific Rim, I describe the formation of a network of community spaces called "hackerspaces" with a focus on their exchange practices and transnational ties. The alternative globalization of hacking through these convivial spaces for socialization and self‐training has created new political locations and horizons, shifting the moral valence of hacking toward more open and collaborative practices. The hackerspace network is one of the key sites for the observation of this transformation for prefiguring new technical and political practices, hence its relevance for anthropological studies of technology and politics in the contemporary moment. [computing, expertise, hacking, technopolitics, hackerspaces]